The unknown followers: Discovery of a new species of SycobiaWalker (Hymenoptera: Epichrysomallinae) associated with Ficus benjamina L. (Moraceae) in the Neotropical region - Farache, Fernando Henrique Antoniolli; Pereira, Cecilia Bernardo; Koschnitzke, Cristiana; Barros, Levi Oliveira; Souza, Elmecelli Moraes de Castro; Felício, Daniel Tirapeli [UNESP]; Gatti, Fabián; Cardona, William; Rasplus, Jean-Yves; Pereira, Rodrigo Augusto Santinelo (Pensoft Publishers, 2018)
Biotic invasion in mutualistic communities is of particular interest due to the possible establishment of new relationships with native species. Ficus species are widely cultivated as ornamental plants, and they host specific communities of chalcid wasps that are strictly associated with the fig inflorescences. Some introduced fig species are capable of establishing new relationships with the local fig wasps, and fig wasp species may also be concomitantly introduced with their host plants. Ficus benjamina L. is widely cultivated across the world, but the associated fig wasps are not reported outside of the species native range. We describe for the first time a non-pollinating fig wasp associated with F. benjamina inflorescences outside its native distribution. Sycobia hodites Farache & Rasplus, sp. n. is the third known species of the genus and was recorded in populations of F. benjamina introduced in the Neotropical region throughout several localities in Argentina, Brazil and Colombia. Sycobia is a gall-inducing non-pollinating fig wasp genus associated with fig trees in the Oriental and Australasian regions. This species competes with pollinators for oviposition sites and may hinder the future establishment of the native pollinator of F. benjamina, Eupristina koningsbergeri Grandi, 1916 in the New World. However, the occurrence of a gall inducing species in this host plant may open ecological opportunities for the establishment of species belonging to other trophic levels such as cleptoparasite and parasitoid wasps.
Keywords: Biocontrol; Chalcidoidea; Dispersal; Invasive species; Parasitoid